Rancang Bangun Aplikasi Sistem Informasi Geografis Pandemik Covid-19 Di Nusa Tenggara Timur - Dwi Prasetyo; Meiton Boru; Viktorianus Ligho (Prosiding SISFOTEK, 2021)
In this era of globalization, the use of information technology in all fields is growing rapidly, because it really helps humans to process data and obtain information quickly, precisely and accurately. Geographic information system is one of the uses of information technology to process maps in digital form, making it easier for the map to be manipulated and processed its data. To find out the spread of Covid 19, it is necessary to develop a system that is able to collect, store, manipulate and display geographic information of the virus distribution area. Through GIS, information on areas affected by the Covid 19 virus can be easily seen on a map view. The description of the distribution of areas of positive patients infected with the virus, patients under surveillance (PDP) and people under surveillance (ODP) is well presented on the map. This distribution map can describe the level of vulnerability of areas exposed to Covid 19 at the city, sub-district and village levels. The grouping in each area is taken based on certain characteristics so that the resulting output is expected to make it easier for users to distinguish the level of vulnerability between one area and another and also display graphs and calculate the number of cases that occurred. The existence of this Geographic Information System can be useful for the community and for policy makers, both the Regional Government, the Ministry of Health, BNPB and other Ministries to increase awareness and self-anticipation in areas prone to the Covid 19 virus.